2006
DOI: 10.1111/j.1365-2249.2006.03091.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing immune function in adult bronchiectasis

Abstract: SummaryBronchiectasis is characterized by chronic airway infection and damage and remains an important health problem. Recent literature has emphasized the role of host defence and immune deficiency in the pathogenesis of bronchiectasis, but there have been few studies of immune function in adult bronchiectasis. A comprehensive screen of immune function was conducted in 103 adult patients with bronchiectasis, encompassing full blood examinations, immunoglobulins and IgG isotypes, complement levels, lymphocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 28 publications
(33 reference statements)
2
31
2
2
Order By: Relevance
“…Airway bacterial colonisation occurs because of impaired mucociliary clearance and because of failure of neutrophil opsonophagocytic killing. Since neutrophils from bronchiectasis patients are believed to be normal prior to their arrival in the airway, it is likely that the airway inflammatory milieu itself impairs bacterial clearance [15,16]. Work over several decades has implicate neutrophil elastase in this process.…”
Section: The Pathophysiology Of Bronchiectasis and The Goals Of Treatmentioning
confidence: 99%
“…Airway bacterial colonisation occurs because of impaired mucociliary clearance and because of failure of neutrophil opsonophagocytic killing. Since neutrophils from bronchiectasis patients are believed to be normal prior to their arrival in the airway, it is likely that the airway inflammatory milieu itself impairs bacterial clearance [15,16]. Work over several decades has implicate neutrophil elastase in this process.…”
Section: The Pathophysiology Of Bronchiectasis and The Goals Of Treatmentioning
confidence: 99%
“…Similarly, King et al 25 showed no major abnormalities in testing of immunoglobulin levels in their cohort. Stead et al 50 also concluded that isolated antibody subclass deficiency was an uncommon cause or association with bronchiectasis in patients beyond the fourth decade.…”
Section: The Significance Of Igg Subclass Deficiencies In Bronchiectasismentioning
confidence: 77%
“…In 2006, King et al 25 demonstrated that phagocytosis was normal in patients with bronchiectasis compared with controls, but that oxidative burst was lower. It was suggested this was either due to a suppressive effect of bacterial products on neutrophil function or an intrinsic defect of neutrophil oxidative burst.…”
Section: Role Of Neutrophils and Neutrophilic Inflammation In Bronchimentioning
confidence: 99%
“…By the way, there is some controversy over whether deficiencies of immunoglobulin G subclasses have a role in the development of bronchiectasis. In a study estimating immune function in adults with bronchectasis, a number of subjects (14%) had low level of immunoglobulin G3, but the significance of this finding was uncertain17. Another small, single center, case-control study showed that almost half (48%) of the patients with bronchiectasis of unknown etiology have low serum concentrations of one or more immunoglobulin G subclasses, and the patients with immunoglobulin subclass deficiency revealed impaired antibody response to H. influenza type b conjugated vaccine18.…”
Section: Immune Deficiencies In Non-cystic Bronchiectasismentioning
confidence: 99%